High‐throughput sequencing for the identification of NOTCH1 mutations in early stage chronic lymphocytic leukaemia: biological and clinical implications. (2nd March 2014) - Lionetti, Marta; Fabris, Sonia; Cutrona, Giovanna; Agnelli, Luca; Ciardullo, Carmela; Matis, Serena; Ciceri, Gabriella; Colombo, Monica; Maura, Francesco; Mosca, Laura; Gentile, Massimo; Recchia, Anna G.; et al.
Summary NOTCH1 mutations have recently emerged as new genetic lesions significantly correlated with survival in chronic lymphocytic leukaemia (CLL). We performed deep next generation sequencing of the NOTCH1 mutation hotspot in 384 cases at diagnosis, including 100 monoclonal B cell lymphocytosis (MBL) and 284 Binet stage A CLL cases, enrolled in the Gruppo Italiano Studio Linfomi O‐CLL1 multicentre trial. The NOTCH1 c.7541_7542delCT dinucleotide deletion was detected and confirmed by an extremely sensitive polymerase chain reaction‐based approach in 11% of MBL and 13·4% of CLL patients. Remarkably, the NOTCH1 mutation was often observed at low clonal level, mainly in MBL patients. Sequential analyses in a fraction of cases showed that the NOTCH1 mutation generally does not occur during the disease course and that the mutational load in positive cases tends to be stable over time. NOTCH1‐mutated cases, even at low clonal level, displayed a significant reduction in median progression‐free survival, although NOTCH1 mutation lost its prognostic impact in a multivariate analysis including 11q and/or 17p deletion, IGHV mutational status, and MBL or CLL status. Our data highlight the importance of using highly sensitive methods to measure NOTCH1 mutations, in order to improve prognostic stratification and obtain useful information for potential therapeutic approaches.